Current account imbalances and income inequality: Theory and evidence - Fares Al-Hussami; Álvaro Martín Remesal (Kiel Institute for the World Economy (IfW), 2012)
In this paper we analyze theoretically and empirically the impact of an increase in income inequality on the current account balance. We develop a model with consumption externalities and heterogeneous agents which explains how an increase in income inequality can affect negatively or positively the current account balance. The relationship is exacerbated by the level of financial liberalization represented by changes in the borrowing constraints. Panel data regressions for a sample of developed and developing economies confirm that an increase in income inequality is mostly linked to a decrease in the current account balance. Moreover, we also find that relatively higher levels of financial liberalization interact with the level of income inequality so that the previous effect is amplified. These results are robust to different specifications.
Keywords: C33; D91; E21; E44; F32; 330; current account; income inequality; global imbalances; financial liberalization; consumption externalities; heterogeneity